Telecommunications and data communications handbook - Horak, Ray; IEEE Xplore (Online Service); Wiley (Hoboken, New Jersey : Wiley-Interscience, 2007)
A practical, accessible survey of telecommunications and data communications services and technologies Finally, there is a commonsense guide to telecommunications and data communications that non-engineers can understand. Popular author Ray Horak provides comprehensive, up-to-date information in plain English, instead of confusing technotalk. Recent developments covered include: . 802.16 and WiMAX . Passive Optical Network (PON) . 802.11g/n . Multiple Input Multiple Output (MIMO) . Broadband over Power Line (BPL) . Instant Messaging . ZigBee In addition, Telecommunications and Data Communications Handbook expands on topics of increasing interest, including: . Fiber Optics . Storage Area Networks (SANs) . Digital Subscriber Line (DSL) . CATV Networks . Wireless, including Bluetooth . Cellular, including 2.5G and 3G, photos, video, and ring tones and ring-back tones . Voice over Internet Protocol (VoIP), including IP PBX and IP Centrex . Session Initiation Protocol (SIP) vs. H.323 Complete with a discussion of the current regulatory and business environments, including divestiture and revestiture as well as mergers and acquisitions, this is the ideal reference for non-engineering professionals in the end-user, carrier, content or service provider, manufacturing, regulatory, or financial communities.
12.14 Video over IP -- 12.15 Multimedia Conferencing -- Applications and Benefits -- References -- 13 THE INTERNET AND WORLD WIDE WEB -- 13.1 The Internet Defined -- 13.2 Internet Physical Topology -- 13.3 Internet Access -- 13.4 Internet Standards, Administration, and Regulation -- 13.5 IP Addressing -- 13.6 Domain Name System -- 13.7 Internet Protocols -- 13.8 Internet Applications -- 13.10 Internet2 -- 13.11 World Wide Web -- 13.12 Intranets and Extranets -- 13.13 Internet Security: A Special Issue -- 13.14 Misuse and Content -- 13.15 Internet Oddities, Screwball Applications, and Some Really Good Ideas -- 13.16 The Dark Side: An Editorial -- References -- 14 NETWORK CONVERGENCE -- 14.1 Convergence Defined -- 14.2 Driving Forces -- 14.3 Conventional Convergence: Wireline Networks -- 14.4 The Race Is On: Mergers and Acquisitions (M&As) -- 14.5 One Potato, Two Potato, Three Potatoe, Four . . . -- 14.6 NexGen Convergence: Wireline and Wireless Networks -- References -- 15 REGULATION: ISSUES AND (SOME) ANSWERS -- 15.1 Telecommunications Act of 1996 -- 15.2 Rates and Tariffs -- 15.3 The Internet -- 15.4 Number Portability -- 15.5 Laws and Sausages -- References -- APPENDIX A ACRONYMS, ABBREVIATIONS, CONTRACTIONS, INITIALISMS, AND SYMBOLS -- APPENDIX B STANDARDS ORGANIZATIONS AND SPECIAL INTEREST GROUPS (SIGs) -- INDEX.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 10/24/2017.
Keywords: Telecommunication -- Handbooks, manuals, etc; Digital communications -- Handbooks, manuals, etc; Electronic books